2019
DOI: 10.3390/ijms20184561
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Graphene-Based Surfaces on the Basic Biological Properties of Human Umbilical Cord Mesenchymal Stem Cells: Implications for Ex Vivo Cell Expansion Aimed at Tissue Repair

Abstract: The potential therapeutic applications of mesenchymal stem/stromal cells (MSCs) and biomaterials have attracted a great amount of interest in the field of biomedical engineering. MSCs are multipotent adult stem cells characterized as cells with specific features, e.g., high differentiation potential, low immunogenicity, immunomodulatory properties, and efficient in vitro expansion ability. Human umbilical cord Wharton’s jelly-derived MSCs (hUC-MSCs) are a new, important cell type that may be used for therapeut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 45 publications
(46 reference statements)
1
18
0
Order By: Relevance
“…Moreover, three different routes of silver nanoparticle synthesis were compared in the creation of the desired homogenous composites with flake graphene. The forms of graphene used (graphene oxide and slightly reduced graphene oxide) are known to be nontoxic towards human cells, for example, mesenchymal stem cells, a finding that was confirmed in our previous work [ 7 ]. This manuscript provides a broad morphological and chemical description of each of the inorganic particles and composites produced in this study.…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Moreover, three different routes of silver nanoparticle synthesis were compared in the creation of the desired homogenous composites with flake graphene. The forms of graphene used (graphene oxide and slightly reduced graphene oxide) are known to be nontoxic towards human cells, for example, mesenchymal stem cells, a finding that was confirmed in our previous work [ 7 ]. This manuscript provides a broad morphological and chemical description of each of the inorganic particles and composites produced in this study.…”
Section: Discussionsupporting
confidence: 76%
“…The biocompatibility of these two graphene derivatives has been confirmed by many publications in the literature [ 6 ]. This aspect of GO and RGO materials presented in this study was also previously investigated by us with human umbilical cord mesenchymal stem cells (hUC-MSCs) [ 7 ]. The overriding conclusion from this study was that none of the tested materials (GO and RGO) were characterized with a negative impact in the cellular viability, proliferation, morphology, or gene expression.…”
Section: Introductionmentioning
confidence: 73%
“…Numerous studies have shown that hUC-MSCs have significant immune modulation and tissue repair functions due to their low immunogenicity [14][15][16]. As an ideal candidate for allogenic adoptive transfer therapy, hUC-MSCs have been shown to play a protective role in A/H5N1-associated acute lung injury [17].…”
Section: Introductionmentioning
confidence: 99%
“…Undoubtedly, it is due to the fact that graphene family materials (GFM) [ 22 ] are unique in so many ways. From graphene, a one-atom-thick sheet of sp 2 -bonded carbon atoms arranged in a honeycomb lattice, to its various derivatives produced by chemical or physical modifications, GFM are known for their exceptional mechanical properties, high thermal and electrical conductivity, high chemical stability, high optical transmittance, large surface area, and many other, often tunable, properties that are exploited in vast number of applications [ 23 , 24 , 25 ]. However, in biomedical fields, two of them, i.e., graphene oxide (GO) and reduced graphene oxide (rGO), are of particular interest.…”
Section: Introductionmentioning
confidence: 99%